2021
DOI: 10.3889/oamjms.2021.7064
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Smartphone Addiction and Insomnia Incidence in Students of the Faculty of Medicine Udayana University Batch of 2020 during the Coronavirus Disease-19 Pandemic

Abstract: BACKGROUND: The use of smartphones is increasing in the coronavirus disease (COVID-19) pandemic for various purposes, this encourages smartphone addiction. In addition, the incidence of insomnia has also increased in the pandemic era. AIM: This study was conducted to find an association between smartphone addiction and the incidence of insomnia, especially among students of the Faculty of Medicine, Udayana University. METHOD: This research is a descriptive-analytic study with the cross-sectional method, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
(85 reference statements)
1
3
0
Order By: Relevance
“…This outcome is comparable to those described in the relevant literature such as in Japan, excessive mobile phone use has been found to be associated with poor sleep hygiene and insomnia [49]. Additionally, it was discovered that the prevalence of insomnia and smartphone addiction were significantly correlated (r = 0.162, p = 0.002) [50].…”
Section: Discussionsupporting
confidence: 83%
“…This outcome is comparable to those described in the relevant literature such as in Japan, excessive mobile phone use has been found to be associated with poor sleep hygiene and insomnia [49]. Additionally, it was discovered that the prevalence of insomnia and smartphone addiction were significantly correlated (r = 0.162, p = 0.002) [50].…”
Section: Discussionsupporting
confidence: 83%
“…7 Khumar et al, 7 conducted a study on smartphone addiction measurement using the SAS-SV score in India, which showed a smartphone addiction prevalence of 44.7%. Based on the study of Indrakusuma et al 6 , on medical students at Udayana University, an analysis of the Smartphone Addiction Scale-Short Version (SAS-SV) questionnaire revealed that most respondents experienced a high level of smartphone addiction (58.24%), while some other students experienced a low level of smartphone addiction (41.76%). 6 In 2020, Leonard et al 9 , surveyed 574 medical students in Malaysia and discovered that 40.6% of them were addicted to smartphones.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the study of Indrakusuma et al 6 , on medical students at Udayana University, an analysis of the Smartphone Addiction Scale-Short Version (SAS-SV) questionnaire revealed that most respondents experienced a high level of smartphone addiction (58.24%), while some other students experienced a low level of smartphone addiction (41.76%). 6 In 2020, Leonard et al 9 , surveyed 574 medical students in Malaysia and discovered that 40.6% of them were addicted to smartphones. Furthermore, according to Research conducted by Serra et al 3 , in 2021, before the COVID-19 pandemic, among 184 people, 31.5% individuals were found to be at high risk of smartphone addiction, and 26.1% had shown smartphone addiction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation